College Entrance Exams: A Modern "Shibboleth"?. Issue 3 (24th May 2022) - Robinson, Daniel; Wainer, Howard
Abstract: The Covid-19 pandemic led many US colleges to drop requirements for admissions tests. Daniel Robinson and Howard Wainer consider what the consequences of this decision might be – for students and universities